1999
DOI: 10.1159/000053491
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 30 Gy Gamma Irradiation on the Quality of Red Blood Cell Concentrates in Several Storage Media

Abstract: Background: The transfusion-associated graft versus host disease (t-GvHD) occurring in immunosuppressed patients can be prevented by irradiation of red blood cell concentrates (RCCs) with gamma irradiation at a dose of 30 Gy prior to transfusion. The aim of this study was to investigate, whether the irradiation of leukocyte-depleted RCCs in different storage media (SAG-M, PAGGS-M, or Adsol) may cause deterioration of red blood cells (RBC), resulting in a shortened shelf life of the RCC. Material and Methods:A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The haematocrit (Hct) is given as a percentage, fHb in mg/dl and Hb total (total haemoglobin) in g/dl [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The haematocrit (Hct) is given as a percentage, fHb in mg/dl and Hb total (total haemoglobin) in g/dl [5].…”
Section: Methodsmentioning
confidence: 99%
“…This is crucial for patients receiving intensive chemotherapy, bone marrow grafts, in utero fetal transfusions or for patients with primary or secondary immunodeficiencies [2,4]. Numerous studies have investigated the effect of gamma irradiation on the quality of RBCs, and found enhanced K + efflux and Na + influx [5–8], reduced ATP levels [7–9] as well as increased free haemoglobin (fHb) and lactate dehydrogenase (LDH) levels in the storage medium of irradiated RBCs as a result of haemolysis [5,8,10]. Limited information is available, however, about the effect of gamma irradiation on the nucleotide metabolism of erythrocytes during storage.…”
Section: Introductionmentioning
confidence: 99%
“…All values were in agreement with data from the literature. [13][14][15][16] At each time point of the study (before storage and at Weeks 1 to 7 of storage), supernatants of C-RBCs and F-RBCs were frozen at -70°C for IL-1RA determination. In addition, for determination of the total (free and cell-associated) IL-1RA content in RBC aliquots, a sequence of freezing (-70°C for 60 min) and thawing (37°C for 15 min) was followed three times to achieve complete cell lysis.…”
Section: Methodsmentioning
confidence: 99%
“…The dose recommended by the US Food and Drug Administration is a minimum of 25 Gy targeted to the midline of the container and a minimum dose of 15 Gy delivered to all other parts of the container [5]. Irradiation of red blood cells (RBCs), however, induces hematologic and biochemical RBC changes, such as K + efflux, Na + influx, reduced adenosine-5 -triphosphate (ATP) levels and increased free hemoglobin [6][7][8], and reduces viability in stored RBCs [9]. Therefore, the US Food and Drug Administration have recommended that RBCs should not be stored more than 28 days from the date of radiation exposure [10].…”
Section: Introductionmentioning
confidence: 99%